Obtaining impact ionization-induced hole current by electrical measurements in gallium nitride metal–insulator–semiconductor high electron mobility transistors. (5th May 2021) - Yeh, Yu-Hsuan; Chang, Ting-Chang; Huang, Wei-Chen; Zheng, Hao-Xuan; Tsao, Yu-Ching; Ciou, Fong-Min; Lin, Yu-Shan; Tan, Yung-Fang; Sun, Li-Chuan; Zhou, Kuan-Ju; Chen, Kuan-Hsu; Huang, Jen-Wei
Abstract: In this paper, an extraction method for measuring impact ionization-induced hole current in gallium nitride (GaN) metal–insulator–semiconductor high electron mobility transistors (MIS-HEMTs) is proposed. The results show that the non-monotonic impact ionization current characteristic can be easily acquired by the extraction method. Further, different hot-carrier stress (HCS) conditions can be obtained based on the I G – V G curve, and the reliability tests can act as verification of the impact-ionization curve. In addition, electrical reliability tests indicate that the threshold voltage ( V TH ) shift and on-state current ( I on ) degradation in the MIS-HEMTs have a positive correlation to impact ionization-generated hole current. During HCS operation, the V TH will shift positively and I on decreases due to hot electrons trapping into the GaN layer. This model is validated by TCAD simulation.